Adsorption of Chromium(VI) Ions from Water by Carbon Nanotubes - Ze-Chao Di; Yan-Hui Li; Zhao-Kun Luan; Ji Liang (Adsorption Science & Technology, 2004)
Carbon nanotubes (CNTs), a new type of carbon material, show exceptional adsorption capability and a high adsorption efficiency for the removal of chromium(VI) ions from water over a broad pH range extending from 4.0 to 7.5. The largest adsorption capacity for CNTs occurred at pH 7.5 and attained a value of 20.56 mg/g at an equilibrium Cr(VI) ion concentration of 33.28 mg/l. The adsorption rate of Cr(VI) ions was fast over the first 20 min with the adsorption capacity of the CNTs reaching 15 mg/g rapidly. The experimental results suggest that CNTs can be employed as good adsorbents for Cr(VI) ions and have great potential for applications in environmental protection.